The Prevalence of Diseases among Refugees Attending the Qatar Fund For Development Clinics in Selangor for the Year 2021 - Kamarul Zaman, Nurazzizu Ain; Ali, Syazana Sirdar; Mohd Zulkifli, Anis Ilany Binti; HS, Arvinder Singh (International Journal of Human and Health Sciences (IJHHS), 2025)
Objectives: The objective of this study was to describe the demographic characteristics of refugees attending Qatar Fund For Development (QFFD) Clinics, which are humanitarian aid clinics, in Selangor in 2021 and determine the prevalence of both Non-Communicable Diseases (NCD) and Communicable Diseases (CD) and the disease prevalence in the highest-occurring nationality. Recognising refugees’ healthcare can pave the way for enhanced services and more policy developments. There is a scarcity of similar data in Malaysia, and this knowledge gap hinders the work that can be done to provide the most favourable welfare to the refugees. These serve as the underlying rationale for conducting this study. Method: A cross-sectional study was conducted among refugees attending three QFFD clinics in Selangor located in Ampang, Selayang, and Kajang utilising secondary data from September to December 2021. This study utilised anonymised data from the clinics’ electronic medical records. There were 14,888 cases available but after removing entries of similar condition, the final data analysed was 12,466. The data was analysed using SPSS version 26.0. Result: From the total, the majority of patients seeking healthcare were Rohingyas (50.3%), Burmese (26.2%), followed by people of other nationalities, Pakistanis, Somalis, Afghans, Indians, Yemenis, and Iranians. 58.7% were females. The mean age of participants was 26.92 years (SD:15.92). From the overall count, diabetes (7.9%, 95%CI= 7.4,8.4) and hypertension (7.2%, 95%CI= 6.8,7.7) were the most common NCDs and COVID-19 (0.4%, 95%CI= 0.3,0.6) was the most common CDs. The most prevalent diseases among Rohingya refugees, the highest-occurring nationality, were upper respiratory tract infections (15%), diabetes (6.2%) and musculoskeletal pain (4.8%). Conclusion: This study highlights significant variations in healthcare utilization among refugees in Malaysia and identifies prevalent health conditions such as respiratory infections, diabetes, and hypertension. This dataset can serve as a benchmark for guiding further screening and investigations into refugee health. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S30